Living Together - Whelan, Gloria (Book collections on Project MUSE., 2013)
Whelan considers a variety of narratives about people coexisting, breaking apart, or coming together. The subdued lives of older women are shaken by a scandalous invasion; a man looks around him to discover he will be living the rest of his life in the wrong place with the wrong people; a married couple, grown apart, find themselves locked together; suburbanites reach out tentatively to the distant city; a house and the ghosts who inhabit it change lives. A final section contains Whelan's novella, "Keeping Your Place," which follows a family as their lives and their home change during the years of the Vietnam War. After the loss of her husband, a mother and the three children must make a final visit to their beloved cabin in the woods and come to a crucial decision.